The Construction of the Fictional World and the Narrative Structure in Symbolic Play Situations in Home Settings - Stein, Alejandra (2017)
The paper presents a longitudinal analysis of the construction of the fictional world and the narrative discourse in play situations registered in the homes of middle-income children from Argentina. Previous research has shown the relations between play and narrative abilities. There are few studies focused on the characteristics of the interaction and the language that contribute to the narrative represented in the play. Sixty play situations were analyzed and registered in the homes of 12 children when they were 2.6 and 3.6 years old respectively. The participants used several resources for the construction of the fictional world of the play. Longitudinal variations were observed regarding the use of metaplay utterances, the types of fictional worlds constructed and the complexity of the narratives.